2023
DOI: 10.3389/fmicb.2023.1169811
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the intestinal microbiome and metabolic profile of patients with cirrhosis supplemented with lactulose, Clostridium butyricum, and Bifidobacterium longum infantis: a randomized placebo-controlled trial

Abstract: BackgroundLiver cirrhosis is commonly accompanied by intestinal dysbiosis and metabolic defects. Many clinical trials have shown microbiota-targeting strategies represent promising interventions for managing cirrhosis and its complications. However, the influences of the intestinal metagenomes and metabolic profiles of patients have not been fully elucidated.MethodsWe administered lactulose, Clostridium butyricum, and Bifidobacterium longum infantis as a synbiotic and used shotgun metagenomics and non-targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…They observed an elevation in B. breve and C. butyricum levels and a reduction in K. pneumoniae. Consequently, there was an enhancement in lipopolysaccharide (LPS) degradation metabolism, an upsurge in butyric acid levels in peripheral blood, and an ultimate improvement in the inflammatory profile [23]. Parallel findings were reported in an animal model by Gómez-Hurtado.…”
Section: Bifidobacterium In Cirrhosissupporting
confidence: 54%
See 3 more Smart Citations
“…They observed an elevation in B. breve and C. butyricum levels and a reduction in K. pneumoniae. Consequently, there was an enhancement in lipopolysaccharide (LPS) degradation metabolism, an upsurge in butyric acid levels in peripheral blood, and an ultimate improvement in the inflammatory profile [23]. Parallel findings were reported in an animal model by Gómez-Hurtado.…”
Section: Bifidobacterium In Cirrhosissupporting
confidence: 54%
“…Collectively, the articles reviewed in this study all aligned in the same direction: Bifidobacterium acts beneficially as a probiotic in NAFLD, ALD, and Cirrhosis. It does so by restoring the intestinal microbiota balance, reducing inflammation and oxidative [23,[28][29][30], whereas (B) represents the same for animal studies [19][20][21][22][24][25][26][27]. The letter "D" denotes the domains present in the checklists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated that botanical drugs and their extracts are capable of suppressing HF by restoring enteric barriers and modulating intestinal dysbacteriosis and metabolites ( Zhao J. et al, 2021 ; Hu et al, 2021 ; Fu et al, 2022 ; Liu et al, 2022 ; Yue et al, 2022 ; Zheng et al, 2022 ; Chang et al, 2023 ; Guo et al, 2023 ; Hu et al, 2023 ). Studies have suggested that probiotics such as Lactobacillus GG ( Bajaj et al, 2014 ), Bacteroides dorei ( Park et al, 2023 ), Clostridium butyricum and Bifidobacterium longum infantis ( Lu et al, 2023 ), as well as gut microbial metabolites such as indole-3-propionic acid ( Sehgal et al, 2021 ; Yuan et al, 2023 ) and Trimethylamine N-oxide ( Zhou D. et al, 2022 ; Nian et al, 2023 ), are beneficial in HF.…”
Section: Introductionmentioning
confidence: 99%